The Future of Work: Redefining Workplace Dynamics, Productivity, Culture, and Employee Well-being Through Remote and Hybrid Models - Akter, Suraiya (Journal of Global Economy, Business and Finance, 2025)
The workplace has experienced a profound transformation, accelerated by the COVID - 19 pandemic and technological advancements. Remote work, once an exception, has become a permanent fixture for many organizations, while hybrid models blending in - office and remote work have emerged as a dominant trend. This paper examines the rise of remote and hybrid work models, exploring their benefits, such as increased flexibility, enhanced productivity, and access to global talent. It also addresses challenges, including maintaining company culture, managing employee well - being, and ensuring equity across remote and in - office employees. The future of work will likely involve continued innovation in work arrangements, with organizations adapting to new expectations and workforce dynamics.